Frontiers of combining systems 8th International Symposium, FroCoS 2011, Saarbrücken, Germany, October 5-7, 2011. Proceedings - Tinelli, Cesare; Sofronie-Stokkermans, Viorica (Lecture notes in computer science. Lecture notes in artificial intelligence, 2011)
This book constitutes the refereed proceedings of the 8th International Symposium on Frontiers of Combining Systems, FroCoS 2011, held in Saarbrücken, Germany, in October 2011. The 15 revised full papers presented together with three invited papers were carefully reviewed and selected from 22 submissions. The event builds a common forum for research activities in the general area of combination, modularization and integration of systems, with emphasis on logic-based ones, and of their practical use.